2014
DOI: 10.1109/jstqe.2013.2294456
|View full text |Cite
|
Sign up to set email alerts
|

Advances Toward Ge/SiGe Quantum-Well Waveguide Modulators at 1.3μm

Abstract: The paper reports on the developments of Ge/SiGe quantum well (QW) waveguide modulators operating at 1.3 μm. Two modulator configurations have been studied: The first one is based on QW structures grown on a 13-μm SiGe buffer on bulk silicon. Light was directly coupled and propagated in Ge/ Si 0 .35 Ge 0 .65 QWs. Using a 3-μm-wide and 50-μm-long modulator, an extinction ratio (ER) up to 6 dB was obtained at 1.3 μm. In the second configuration, the aim is to integrate Ge/SiGe QW on standard silicon-on-insulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…For the integration with Si WGs, the thickness of relaxed SiGe buffer layer beneath the Ge/GeSi quantum wells should be reduced [84]. The operation at shorter wavelengths around 1.3 µm could be obtained with a precise control of Ge well thickness [86,87].…”
Section: Low-power Optical Modulatorsmentioning
confidence: 99%
“…For the integration with Si WGs, the thickness of relaxed SiGe buffer layer beneath the Ge/GeSi quantum wells should be reduced [84]. The operation at shorter wavelengths around 1.3 µm could be obtained with a precise control of Ge well thickness [86,87].…”
Section: Low-power Optical Modulatorsmentioning
confidence: 99%
“…Lever et al [51] and Rouifed et al [52] experimentally reported QCSE from photocurrent measurements around the optical wavelength of 1.3 µm using a similar structure of strain-balanced Ge/SiGe MQWs on Si 0.22 Ge 0.78 and Si 0.21 Ge 0.79 relaxed buffers, respectively. In 2014, Rouifed et al [53] experimentally reported a 3-µm-wide and 50-µm-long Ge/SiGe MQW optical modulator operating in the O-band telecommunication wavelength. The modulator exhibited a 5-dB ER with 4-dB IL for a voltage swing of 3 V between 4 and 7 V at the optical wavelength of~1295 nm.…”
Section: Ge/sige Quantum Well Optical Modulatorsmentioning
confidence: 99%
“…Such integration requires a reduction of the thickness of the buffer layer between Ge/SiGe QW and silicon wafer. To this purpose, we developed a relaxed buffer with 360nm thickness that would practically allow the optical coupling between a SOI waveguide and the Ge/SiGe QW active region [9]. We then theoretically investigated properties of a QW modulator integrated on SOI waveguides.…”
Section: Waveguide Integrationmentioning
confidence: 99%